Assessment of Quality of Life of People who Stutter: A Cross-sectional Study. (March 2014) - Bajaj, Gagan; Varghese, Aiswarya Liz; Bhat, Jayashree S.; Deepthi, Joylin
Stuttering is a complex communication disorder that impedes the normal flow and pattern of speech, which is characterized by involuntary audible or inaudible pause, repetitions, prolongations, blocks, etc. Other than the core behaviors, people who stutter experience various other problems such as fear, anxiety, depression, shame, etc., which can in turn affect the quality of life (QOL). The purpose of this study is to develop a questionnaire in order to assess the QOL of people who stutter. A total of 30 participants aged between 18 and 30 years were enrolled for the study. Out of the stutterers included, 15 were employed and 15 were non-employed/students. The study was carried out in two phases. The first phase involved the development of a questionnaire based on literature search and available tests. The second phase involved administering the validated questionnaire on the participants. The questionnaire consisted of six domains targeting (1) speech-related fear and anxiety, (2) interpersonal and social relationships, (3) behavioral reaction to stuttering, (4) educational status, (5) employment and job opportunity, and (6) effect of speech therapy. For each item, response scales were organized (2—almost always, 1—sometime, 0—not at all). Developed questionnaire showed good content validity for all the domains and questions. The result of Cronbach's alpha for each domain indicates moderate internal consistency and excellent internal consistency for the overall questionnaire. Multiple domains were observed to be affected among adults who stutter, and the differences were not found to be significantly different as compared to the available QOL data from other cultural settings.